A articulação pedagógica como prática de gestão escolar: caminhos possíveis para a qualificação dos processos pedagógicos - Fonseca, Eliana Maria Bomfim (Universidade do Vale do Rio dos Sinos, 2021)
This research had as its central theme the pedagogical articulation, had the participation of a group of pedagogical coordinators of a private institution in Salvador and started from the following problematization "how does pedagogical articulation contribute or can contribute to the qualification of pedagogical processes and practices developed and accompanied by the pedagogical coordinators of elementary school at Antônio Vieira College?". The work was organized in four chapters that dealt with: the academic and professional trajectory of the author and her concerns; the methodological paths, having in the questionnaire and in the focus group the possibility of spaces for collecting empirical data and spaces for formation, reflection and construction; theoretical subsidies from the shift of emphasis from administration to school management, the historicity of school supervision, the attributions of pedagogical coordination and cooperation as a central theme in the performance of pedagogical articulation; the analyses performed from the transcriptions of the meetings of the focus group and the presentation of the final product. . The concerns of the research dialogued with authors who deal with teaching knowledge, as Maurice Tardif (2002) and Selma Garrido Pimenta (1999), who discuss teacher training, such as Antônio Nóvoa (1992 and 2009), Veiga Neto (2015) and Isabel Alarcão (2001) and who discuss pedagogical articulation, in the bias of cooperation, with Richard Sennett (2012). The study presented two final products: (a) the formative process of pedagogical coordinators from the development of the focus group, because, at the same time that it served as a space for production and data collection, it had a formative function; and (b) indicative for the construction of an action plan for the pedagogical articulation.
Keywords: Articulação pedagógica; Coordenação pedagógica; Gestão educacional; Grupo focal; Plano de ação; Pedagogical articulation; Pedagogical coordination; Educational management; Focus group; Action plan; ACCNPQ::Ciências Humanas::Educação